Concentrations of microcystins in tissues of several fish species from freshwater reservoirs and ponds - Kopp, Radovan; Palíková, Miroslava; Adamovský, Ondřej; Ziková, Andrea; Navrátil, Stanislav; Kohoutek, Jiří; Mareš, Jan; Bláha, Luděk (Environmental monitoring and assessment, 2013)
The aim of this study is to summarise the determination of concentrations of microcystins (MCs) in muscle and liver of freshwater fish species caught in stagnant waters of the Czech Republic. Within the years 2007-2009, 351 muscle samples and 291 liver samples of 16 freshwater fish species derived from four fishponds, and four water reservoirs were analysed. MCs were detected in 53 liver samples. The highest concentrations of microcystins were determined in liver samples of carnivorous fish species; 50.3 ng/g of fresh weight (FW) in perch (Perca fluviatilis) and 22.7 ng/g FW in pikeperch (Sander lucioperca). MCs in liver were detected in other five fish species; asp (Aspius aspius), pike (Esox lucius), common carp (Cyprinus carpio), grass carp (Ctenopharyngodon idella) and European eel (Anguilla anguilla). Concentrations of MCs in liver of nine fish species (European bream, whitefish, tench, silver carp, European catfish, roach, chub, crucian carp and rudd) were below the detection limit of 1.2-5.4 ng/g FW for different MC congeners. However, the concentrations of MCs in all muscle samples were below the detection limit. The assessment of MCs concentrations might be influenced by the detection method used. Due to the concentrations of MCs being below the detection limit in muscle samples of all fish species analysed, it seems that there might be a low potential threat for human health in case of fish muscle consumption.
Keywords: Česká republika; ryby; chemické látky znečišťující vodu; Czech Republic; mikrocystiny; Fishes; Environmental Monitoring; Muscles; Water Pollutants, Chemical; Animals; Liver; svaly; sladká voda; játra; Fresh Water; Microcystins; monitorování životního prostředí; zvířata